Group-Based Mobile Messaging in Support of the Social Side of Leisure - Counts, Scott (Computer Supported Cooperative Work (CSCW), 2007)
Communication on mobile devices plays an important role in people’s use of technology for leisure, but to date this communication has largely been one-to-one. Mobile internet connectivity can support a variety of group-based messaging and media sharing scenarios. Switching to group-based messaging should enhance the social and leisure aspects of the communication, but in what ways and to what extent? An experimental system for text and photo messaging on mobile devices was tested in a research deployment to four groups of 6–8 participants who used both a group-based and one-to-one version of the system. Results highlight a significant increase in message sending, in mobile device “fun”, and in the social qualities of mobile communication when messaging group-wide, along with a few minor costs. Qualitative feedback provides further explanation of the social benefits.